Processes and mechanisms in remediation of aqueous chromium contamination by sulfidated nano-scale zerovalent iron (S-nZVI): experimental and computational investigations - Wang, Yuanyuan; Yang, Yuesuo; Shi, Jinyu; An, Wengang; Lyu, Tao; Zhang, Ping (Elsevier, 2024)
Sulfidated nano-scale zerovalent iron (S-nZVI) has emerged as an advanced functional nanomaterial for efficiently remediating Cr(VI) contamination in aqueous environments. However, there is an insufficient understanding of its coherent process, removal pathway, and hydrochemical reactive mechanisms, presenting potential challenges for its future environmental applications. To address this gap, this study successfully synthesized S-nZVI through a chemical precipitation method and effectively applied it for the removal of Cr(VI). Additional characterization revealed that the removal of Cr(VI) followed a sequence of rapid chemisorption and intraparticle diffusion processes, concomitant with an increase in pH and a decrease in oxidation-reduction potential. The remediation mechanism encompassed a synergistic reduction of Cr(VI) to Cr(III) and simultaneous immobilization via Cr2FeO4 coprecipitation. The highest Cr(VI) removal capacity of 75 mg/g was attained during dynamic removal experiments in the sand column packed with S-nZVI. Further computational analysis, employing density functional theory calculations based on the experimental data, revealed the involvement of multiple molecular orbitals of Cr(VI) in the removal process. It also elucidated a step-by-step reduction pathway for Cr(VI) characterized by decreasing free energy. These findings provide evidence-based insights into Cr(VI) remediation using S-nZVI and can serve as valuable technical support for future environmental management of heavy metals.
Keywords: S-nZVI; chromium; adsorption; co-precipitation; DFT computation